Cryptolepine Suppresses Colorectal Cancer Cell Proliferation, Stemness, and Metastatic Processes by Inhibiting WNT/β-Catenin Signaling - Jude Tetteh Quarshie; Kwadwo Fosu; Nicholas Awuku Offei; Augustine Kojo Sobo; Osbourne Quaye; Anastasia Rosebud Aikins (MDPI AG, 2023)
Colorectal cancer (CRC) is the third most frequent cancer and the second leading cause of cancer-related deaths globally. Evidence shows that over 90% of CRC cases are initiated by a deregulated Wingless Integrated Type-1 (WNT)/β-catenin signaling pathway. The WNT/β-catenin pathway also promotes CRC cell proliferation, stemness, and metastasis. Therefore, modulators of the WNT/β-catenin pathway may serve as promising regimens for CRC. This study investigated the effect of cryptolepine-a plant-derived compound-on the WNT/β-catenin pathway in CRC. Two CRC cell lines, COLO205 and DLD1, were treated with cryptolepine or XAV 939 (a WNT inhibitor) in the presence or absence of WNT3a (a WNT activator). Using a tetrazolium-based assay, cryptolepine was found to reduce cell viability in a dose- and time-dependent manner and was a more potent inhibitor of viability than XAV 939. RT-qPCR analyses showed that cryptolepine reverses WNT3a-induced expression of β-catenin, c-MYC, and WISP1, suggesting that cryptolepine inhibits WNT3a-mediated activation of WNT/β-catenin signaling. Cryptolepine also repressed WNT3a-induced OCT4 and CD133 expression and suppressed colony formation of the cells, indicating that cryptolepine inhibits the stemness of CRC cells. Additionally, cryptolepine inhibited WNT3a-induced epithelial-to-mesenchymal transition by reducing the expression of SNAI1 and TWIST1 genes. In a wound healing assay, cryptolepine was found to suppress cell migration under unstimulated and WNT3a-stimulated conditions. Moreover, cryptolepine downregulated WNT3a-induced expression of MMP2 and MMP9 genes, which are involved in cancer cell invasion. Altogether, cryptolepine suppresses CRC cell proliferation, stemness, and metastatic properties by inhibiting WNT3a-mediated activation of the WNT/β-catenin signaling pathway. These findings provide a rationale for considering cryptolepine as a potential WNT inhibitor in CRC.